Environmental management in tourism and hospitality - Bieloborodova M.; Bezuhla L.; Herasymenko T.; Kamushkov O. (My University, 2025)
The textbook is designed for full-time and part-time master’s students of specialties 241 Hotel and restaurant business (J2 Hotel, restaurants and catering) and 242 Tourism and Recreation (J3 Tourism and recreation). The textbook includes theoretical materials, practical case studies, and the best examples of international and domestic practices in environmental management within the hospitality sector. The textbook contains open-ended questions and tests to check the level of mastery of the material presented and can be used to organize independent work of students.
Екологічне управління в туризмі та гостинності
Keywords: екологічне управління в туризмі; екологічне управління в гостинності